On the alignment of velocity and magnetic fields within magnetosheath jets - Plaschke F; Jernej M; Hietala H; Vuorinen L (COPERNICUS GESELLSCHAFT MBH, 2025)
Jets in the subsolar magnetosheath are localized enhancements in dynamic pressure that are able to propagate all the way from the bow shock to the magnetopause. Due to their excess velocity with respect to their environment, they push slower ambient plasma out of their way, creating a vortical plasma motion in and around them. Simulations and case study results suggest that jets also modify the magnetic field in the magnetosheath on their passage, aligning it more with their velocity. Based on Magnetospheric Multi-scale (MMS) jet observations and corresponding superposed epoch analyses of the angles phi between the velocity and magnetic fields, we can confirm that this suggestion is correct. However, while the alignment is more significant for faster than for slower jets, and for jets observed close to the bow shock, the overall effect is small: typically, reductions in phi of around 10 degrees are observed at jet core regions, where the jets' velocities are largest. Furthermore, time series of phi pertaining to individual jets significantly deviate from the superposed epoch analysis results. They usually exhibit large variations over the entire range of phi: 0 to 90 degrees. This variability is commonly somewhat larger within jets than outside them, masking the systematic decrease in phi at core regions of individual jets.